Pengaruh Kompensasi Rugi Fiskal,Return on Asset,Leverage, dan Sales Growth terhadap Tax Avoidance - Selly Ariyanti Lestari; Hesty Ervianni Zulaecha; Imam Hidayat; Samino Hendrianto (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2022)
The purpose of this study is to determine the effect of Fiscal Loss compensation, Return On Assets, Leverage, and Sales growth, on tax avoidance in the chemical industry sector listed on the Indonesia Stock Exchange (IDX). The research period used is 4 years period 2017-2019.The population of this study includes all companies in the basic and chemical industry sectors listed on the Indonesia Stock Exchange (IDX) for the period 2017-2019. The analysis used is panel data logistic regression analysis.The results showed that Return on Assets had a negative effect on Tax Avoidance, Fiscal Loss Compensation, Leverage, Sales Growth, did not have a significant effect on tax avoidance.The data analysis technique used in this study is multiple linear regression and processed using the Eviews 9.0 program.